PENGARUH POJOK BEI UDINUS DALAM MENINGKATKAN MOTIVASI BELAJAR MAHASISWA DI BIDANG PASAR MODAL DENGAN KECERDASAN EMOSIONAL SEBAGAI PEMODERASI - Pratiwi, Ririh Dian; Kadarningsih, Ana Kadarningsih (JURNAL PENELITIAN EKONOMI DAN BISNIS, 2013)
Recently, education have increasingly widespread but learning motivation has decreased.          A college has a role in improving student learning motivation and provide technology-based learning tools especially in studying the science of investment and capital markets. The purpose of this research is to test the influences Udinus Corner IDX to increase student learning motivation in capital market with emotional intelligence as moderation variable. The samples size of this research is 46 students from 63 visitors Udinus Corner IDX in Juni 2013. Using SPSS 16.00 for Windows, the results shows that variable Udinus Corner IDX and emotional intelligence have no influence on learning motivation in capital market and emotional intelligence is not suitable as moderation variable. Keywords : Corner IDX, emotional intelligence